Exploring the phytochemical constituents of Aegle marmelos (bael) and their therapeutic potential against chronic diseases - Sahoo, Lopamudra; Nayak, Yashaswi; Mohanty, Sanjib Kumar (International Journal of Basic & Clinical Pharmacology, 2025)
Aegle marmelos (Bael), a highly esteemed plant in traditional medicine, is recognized for its remarkable therapeutic properties, attributed to its rich and diverse phytochemical composition. The plant contains bioactive compounds such as alkaloids, flavonoids, tannins, phenolic acids, coumarins and essential oils, which contribute to its pharmacological activities. These compounds exhibit potent antioxidant, anti-inflammatory, antidiabetic, antimicrobial, hepatoprotective and cardioprotective effects, positioning Bael as a promising natural remedy for managing chronic diseases. Bael has demonstrated significant efficacy in regulating blood glucose levels, enhancing insulin sensitivity and protecting pancreatic beta cells, making it an effective agent in diabetes management. Additionally, its strong antioxidant and anti-inflammatory activities are essential in combating oxidative stress and chronic inflammation, which are key drivers of metabolic and neurodegenerative disorders. Bael’s antimicrobial properties further expand its potential to address infections and gastrointestinal issues. However, the integration of Aegle marmelosinto mainstream medicine faces challenges, including variability in its phytochemical composition, lack of standardized formulations and insufficient clinical trials to validate its safety and efficacy. This review aims to comprehensively explore the phytochemical constituents of Aegle marmelosand their therapeutic potential, particularly against chronic diseases. By identifying research gaps and future directions, it seeks to support the development of Bael as a reliable, standardized and effective therapeutic agent for modern healthcare.